Proposta de intervenção fonoaudiológica com jogos teatrais na doença de Parkinson: estudo de caso clínico - Felisette, Roberto Correia de Mello (2012)
Introduction: in the clinical practice of Speech-Language Pathologists, the patient with Parkinson disease (PD) is submitted to methods which focus on the physiological aspects of the voice. Aim: to analyze, through a clinical case study, the stages of a Speech-Language Pathology therapeutic process with theater games in a patient with PD. Method: this descriptive, retrospective, exploratory study had the participation of a male, 63 year old subject, who was medically diagnosed with PD at age 59. Twenty therapy sessions (total of 20 hours) were conducted in the period in between March and October 2010, which were divided into two separate moments: vocal training techniques and activities involving Theater Games. Speech samples consisted of audio and video recordings of the utterance of a sustained vowel /a/, naming days of the week, and the patient s comments about his voice. These samples were collected in three different moments: before the intervention, during the 10th therapy session and after the intervention. The recordings were submitted to perceptual auditory assessment where vocal quality parameters of pitch, loudness, general level of tension, speech speed, articulation and facial expressions were considered. The therapy process was registered in both audio and video recordings and also relying on accounts from the therapist s memory. The data were analyzed according to the proposal of Theater Games in five steps: complaint, understanding of the signs and symptoms of PD, compliance to treatment, expressiveness techniques and daily-life experiences. Clinical Case Presentation: the patient complained, over the past months, of isolation from conversational situations and from contact with people. During the therapy sessions, activities related to improving vocal projection, extension and sound articulation were performed in alternation with dynamics that involved theater games. The employment of strategies with relational focus allowed the Speech- Language Therapeutic intervention to be carried out while it was making sense for the patient. He performed several exercises in order to improve voice and articulation and worked in a relational and dialogical context which was similar to his daily life experiences. The use of Theater Games favored this possibility. Switching roles in the moment when the Theater Games were performed reinforced the context of the situation proposed by the game (player and audience). Speech assessment suggests a better communication pattern of the patient, with his accounts of an increasing communicative and social insertion. Final Remarks: The proposition of a method which used both a physiological focus of vocal production alongside relational communication activities through Theater Games suggests positive effects on the patient who participated in this study